Simulasi Pembuatan Jaringan Peer To Peer Menggunakan Cisco Paket Tracer - Ratnasari Ratnasari; Selpi Amanda Fadillah; Rahima Mahabbah; Ismah Nurul Sya’bani; Alfi Manarul Huda; Didik Aribowo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Data communication is a field of science that studies the process of sending data, as well as how data can be received from sending and receiving terminals. A computer network is a set of